Joseph Coolidge papers - Coolidge, Joseph, 1773-1840.
Chiefly letters (1793-1795) written by Coolidge to his future wife, Eliza Bulfinch, during his travels in Europe.
Massachusetts railroad pioneer and a founder of Massachusetts General Hospital, Boston. Married Elizabeth "Eliza" Bulfinch (1777-1837) in 1796.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Coolidge, Elizabeth Bulfinch -- Correspondence; Europe -- Description and travel; Railroad executives